2020
DOI: 10.1007/s11332-020-00630-w
|View full text |Cite
|
Sign up to set email alerts
|

Performance trends in Paralympic athletes in sprint, middle-distance and endurance events

Abstract: In recent decades the participation in Paralympic sports has grown exponentially, with an increasing number of countries and athletes attending to these events. However, despite the tremendous growth, only a few studies involving the performance of Paralympic athletes have been published to date. We aimed to investigate and compare the performance trends of men and women in category T54 from sprint, middle-distance and endurance events in Paralympic international events held from 2009 to 2018. Data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Men had better performances than women, confirming results from other studies in both sports with and without disabilities (de Macedo et al, 2020; Thibault et al, 2010). Our results also show that the track-and-field performance level was related to the level of visual impairment in male athletes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Men had better performances than women, confirming results from other studies in both sports with and without disabilities (de Macedo et al, 2020; Thibault et al, 2010). Our results also show that the track-and-field performance level was related to the level of visual impairment in male athletes.…”
Section: Discussionsupporting
confidence: 87%
“…One of the few studies on this subject (Grobler et al, 2015) showed a progression of sprint performances (100 and 200 m finals) of athletes with disabilities (visual impairments, amputations, and cerebral palsy) between 1992 and 2012, which largely surpassed the progression of Olympic athletes. More recently, a study focused on the performance of Paralympic athletes from the category T54 (wheelchair competitors or those with spinal cord injuries) concluded that there were no significant changes in their performance between 2009 and 2018 in sprint, middle- and long-distance events (de Macedo et al, 2020).…”
mentioning
confidence: 99%
“…Exceptional performances are limited by physiological and genetic conditions, economic and environmental contexts and a participant population mostly consisting of athletes with optimized traits 13 . For Paralympic athletes, according to some disciplines, events and classifications, performance has increased slightly or not significantly over the past few years in Track & Field 19,20 and Para swimming 21 . An overall trend for improved Paralympic sprint performances in athletes with lower-limb amputations since 1992 to 2012 was observed with a consequent role played by runningspecific prostheses 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Performance in WheelChair Racing (WCR) has greatly improved since the emergence of this sport in the 1950s [ 1 ] due to its professionalization and to the technological improvements in wheelchair design and manufacturing [ 2 ]. However, this trend has slowed drastically over the past decade to the point that no significant improvement in performance has been observed between 2009 and 2018 [ 3 ]. Performance in WCR can be defined as the time required to complete a given distance, making the evolution of manual wheelchair (MWC) speed during the race the main outcome parameter to study.…”
Section: Introductionmentioning
confidence: 99%